Extracting the principles of sustainability from the architecture of colonial hospitals in Malaysia: appreciating the past wisdoms as best practices - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Aripin, Srazali; Abdul Majid, Noor Hanita; Denan, Zuraini; Sanusi, Aliyah Nur Zafirah (2014)
Malaysia’s sturdy hospital buildings built by the colonial government throughout the country are still in use today. These hospitals had withstood years of operation and had contributed, together with the current hospital buildings, in improving the health and well-being of Malaysians today. Hospitals are both expensive to build and to maintain. The quest for sustainable design includes the evaluation of performances of both old and modern hospitals buildings for future guidance. This paper focuses on the performances of selected colonial hospital buildings in Malaysia in-use. The objective is to learn, understand and extract the good values and wisdoms from the past planning and design legacies as best practices. Qualitative approaches adopted for this study include content analysis of relevant literature; fieldwork survey; random interviews and observations. The study analysed the hospital locations, its site planning, building massing, building attributes and its environmental performances on thermal comfort, visual, day-lighting and ventilation. Findings of the study provide practical recommendations on criteria for site selection,site planning, building configuration, building depths and widths, and openings for ventilation and day-lighting. Limitation includes the duration and number of buildings studied within the stipulated time frame as well as permission to access the site. Significance of this study is the collection of the past best practices on the hospital design physical sustainable attributes that are evergreen before it slowly disappears in time.